No easy fix : global responses to internal wars and crimes against humanity - Marchak, M. Patricia, 1936-2010 (Studies in nationalism and ethnic conflict., 2008)
"Bringing together her own field interviews, documentary material, and secondary sources, Patricia Marchak critically assesses the recent history of international interventions and criminal prosecutions. She examines three cases in detail - Cambodia, Rwanda, and the former Yugoslavia in its current forms of Bosnia and Serbia - considering their international context prior to and during internal wars and arguing that each case has to be understood in its own context and history. There is no common pattern and no easy fix that can mend broken societies after wars."--Jacket